Determining source strength of semivolatile organic compounds using measured concentrations in indoor dust. (31st October 2013) - Shin, H.‐M.; McKone, T. E.; Nishioka, M. G.; Fallin, M. D.; Croen, L. A.; Hertz‐Picciotto, I.; Newschaffer, C. J.; Bennett, D. H.
Abstract Consumer products and building materials emit a number of semivolatile organic compounds (SVOCs) in the indoor environment. Because indoor SVOCs accumulate in dust, we explore the use of dust to determine source strength and report here on analysis of dust samples collected in 30 US homes for six phthalates, four personal care product ingredients, and five flame retardants. We then use a fugacity‐based indoor mass balance model to estimate the whole‐house emission rates of SVOCs that would account for the measured dust concentrations. Di‐2‐ethylhexyl phthalate (DEHP) and di‐iso‐nonyl phthalate (DiNP) were the most abundant compounds in these dust samples. On the other hand, the estimated emission rate of diethyl phthalate is the largest among phthalates, although its dust concentration is over two orders of magnitude smaller than DEHP and DiNP. The magnitude of the estimated emission rate that corresponds to the measured dust concentration is found to be inversely correlated with the vapor pressure of the compound, indicating that dust concentrations alone cannot be used to determine which compounds have the greatest emission rates. The combined dust‐assay modeling approach shows promise for estimating indoor emission rates for SVOCs.